Functional outcomes and rehabilitation effi ciency in patients with restricted weight-bearing - Meredith Ogilvie-Brown; Tik Chan (Annals of Musculoskeletal Medicine - Peertechz Publications, 2019)
Orthopaedic injuries can require a period of restricted weight-bearing which can increase inpatient hospital admissions and place the patient at risk of the complications of immobility. This study aimed to identify the functional outcomes and rehabilitation effi ciency for patients admitted to rehabilitation with restricted weight bearing. Method: Patients admitted to Brighton Rehabilitation Unit between 1 January 2015 to 31 December 2016 with weight-bearing restrictions for either upper or lower limbs were included in the study. Analysis of data for LOS, duration of restriction, complications and Functional Independent Measure scores were used to compare to all the admissions to the unit during 2015.